Design, synthesis and biological assessment of new 1-benzyl-4-((4-oxoquinazolin-3(4H)-yl)methyl) pyridin-1-ium derivatives (BOPs) as potential dual inhibitors of acetylcholinesterase and butyrylcholinesterase. Issue 4 (April 2021) - Zarei, Samaneh; Shafiei, Mohammad; Firouzi, Maryam; Firoozpour, Loghman; Divsalar, Kouros; Asadipour, Ali; Akbarzadeh, Tahmineh; Foroumadi, Alireza
Abstract: Alzheimer's disease (AD), is among the most growing neurodegenerative diseases, which is mainly caused by the acetylcholine neurotransmitter loss in the hippocampus and cortex. Emerging of the dual Acetylcholinesterase (AChE)/Butyrylcholinesterase (BuChE) inhibitors has increased for treating Alzheimer disease. In this study, we would like to report the design and synthesis of a new sequence of 1-benzyl-4-((4-oxoquinazolin-3(4 H )-yl)methyl) pyridin-1-ium derivatives (BOPs) assessed as BuChE and AChE inhibitors. Ellman's approach was used for the evaluation of AChE and BuChE inhibitory activities. Moreover, docking research was conducted to predict the action mechanism. Among all synthesized compounds, 1-(3-bromobenzyl)-3-((4-oxoquinazolin-3(4 H )-yl)methyl) pyridin-1-ium bromide (BOP-1) was found to be the most active compound with dual activity for inhibition of AChE (IC50 = 5.90 ± 0.07μM), and BuChE (IC50 = 6.76 ± 0.04μM) and 1-(4-chlorobenzyl)-3-((6, 7-dimethoxy-4-oxoquinazolin-3(4 H )-yl)methyl) pyridin-1-ium chloride (BOP-8) showed the highest AChE inhibitory activity (IC50 s = 1.11 ± 0.09 μM). The synthesized compounds BOP-1 and BOP-8 could be proposed as valuable lead compounds for further drug discovery development against AD. Abstract : Alzheimer's disease; Chloinestrases; Oxoquinazolin; pyridinuim salts; In-vitro assay.